Natural landscapes of Sortavala Archipelago islands of northern part of the lake Ladogaartificially-induced by old mining workings - Borisov, Igor (Naturalne krajobrazy archipelagu Sortavala w północnej części jeziora Ładoga sztuczniezmodyfikowane dawnymi wyrobiskami górniczymi, 2017)
Artificially-induced natural landscapes, produced by the interaction of natural processes and mining in the 1770s–1950s, make up a large part of modern landscapes in the northern Lake Ladoga area, Republic of Karelia, Russia. Mine workings have become a common part of modern landscapes in the region. They were formed in various periods of time in various physico-geographic environments and are preserved to a varying degree. Therefore, they are of great interest from the point of view of the evolution of artificially-induced complexes and tourism.
Hereditas Minariorum, Vol. IV, 2017, s. 123-134
Keywords: górnictwo; historia; kultura materialna; archeologia przemysłowa; northern Lake Ladoga area; Russia; artificially-induced landscapes; mining workings; mining-industrial heritage